Sosiologi Lembaga Pendidikan: Kolaborasi Guru, Orang Tua, dan Komunitas Lokal dalam Mendukung Pendidikan Anak Berkebutuhan Khusus di SD Al Irsyad Al Islamiyyah 01 Purwokerto - Nurul Hidayani; Muh Hanif (PROGRAM STUDI PAI STIT TANGGAMUS, 2026)
This article is designed to examine the Collaboration of Teachers, Parents, and the Local Community in Supporting the Education of Children with Special Needs at SD Al Irsyad Al Islamiyyah 01 Purwokerto through the perspective of a sociological educational institution. The article’s main focus is directed at the claim that the success of the education of children with special needs in Islamic Elementary Schools is highly dependent on the collaboration of teachers, parents, and the local community as a social support network. The research needs to be located in schools or madrasas that empirically demonstrate social practices related to this issue. Primary data can be obtained through observations of teachers and interviews with involved educational actors, as well as documentation of institutional policies, programs, and practices. By using a qualitative approach, this article is expected to be able to show how social relations, institutional norms, educational authorities, and the experiences of students/teachers/parents shape daily educational practices.